Metabolome Analysis of Constituents in Membrane Vesicles for Clostridium thermocellum Growth Stimulation - Shunsuke Ichikawa; Yoichiro Tsuge; Shuichi Karita (Microorganisms, 2021)
The cultivation of the cellulolytic bacterium, Clostridium thermocellum, can have cost-effective cellulosic biomass utilizations, such as consolidated bioprocessing, simultaneous biological enzyme production and saccharification. However, these processes require a longer cultivation term of approximately 1 week. We demonstrate that constituents of the C. thermocellum membrane vesicle fraction significantly promoted the growth rate of C. thermocellum. Similarly, cell-free Bacillus subtilis broth was able to increase C. thermocellum growth rate, while several B. subtilis single-gene deletion mutants, e.g., yxeJ, yxeH, ahpC, yxdK, iolF, decreased the growth stimulation ability. Metabolome analysis revealed signal compounds for cell–cell communication in the C. thermocellum membrane vesicle fraction (ethyl 2-decenoate, ethyl 4-decenoate, and 2-dodecenoic acid) and B. subtilis broth (nicotinamide, indole-3-carboxaldehyde, urocanic acid, nopaline, and 6-paradol). These findings suggest that the constituents in membrane vesicles from C. thermocellum and B. subtilis could promote C. thermocellum growth, leading to improved efficiency of cellulosic biomass utilization.